PASQUALE - A long-term partnership to improve hand hygiene and capacity building in infection prevention and control in the Faranah region of Guinea - Anna Borodova; Aziz Amadou Diallo; Rebekah Wood; Ousmane Tounkara; Carlos Rocha; Mouctar Bayo; Lena Landsmann; Mahamoud Sama Cherif; Matthias Borchert; Carolin Meinus; Ibrahima Nabé; Sekou Doumbouya; et al. (Elsevier, 2024)
Across the globe, hand hygiene (HH) is promoted to fight the spread of healthcare associated infections. Despite multiple ongoing HH campaigns and projects, the healthcare associated infection rates remain high especially in low- and middle-income countries. In the narrative overview presented here, we aim to share objectives, framework, successes and challenges of our long-term partnership in Guinea to offer guidance for other projects aiming to sustainably improve HH.